Combined Sugarcane Pretreatment for the Generation of Ethanol and Value-Added Products - Bordignon, Sidnei Emilio; Ximenes, Eduardo; Perrone, Olavo Micali; Carreira Nunes, Christiane da Costa; Kim, Daehwan; Boscolo, Maurício; Gomes, Eleni; Filho, Edivaldo Ximenes Ferreira; da Silva, Roberto; Ladisch, Michael R. (Frontiers in Energy Research, 2022)
In this work, we tested individually and combined application of ozonolysis and liquid hot water (LHW) to pretreat sugarcane bagasse (SCB) for removal of enzyme and/or microbial inhibitors and generation of potential value-added chemicals. A solid content with 80% cellulose and a liquid phase (liquor) rich in phenolic derived compounds from lignin (3 g.L-1), sugars (>20 g.L-1) and other compounds, such as furfural and hydroxymethylfurfural (HMF), were generated. Compared to individual treatments, maximal (59%) glucan conversion occurred in the presence of double-pretreated bagasse, which had 32-50% more glucan available than the samples individually LHW or ozone-pretreated. The maximal ethanol production was also obtained with double-pretreated SCB enzyme hydrolysate (92% after 42 hours). In summary, this work showed that ozone reacts effectively with lignin without the use of any other chemical reagent, and LHW pretreatment, followed by a washing step, was effective in solubilizing and clean up the fibers from enzyme and microbial inhibitory compounds, including phenolics after ozone attack. Moreover, the generated cellulose-rich substrate is promptly fermentable. The acid liquor fraction, removed by sequential washings and containing mainly sugars and phenolic compounds, can be explored in potential uses for green chemistry bioconversions processes.